Research on Members Network Marketing Strategy Based on User Retention Growth Model - Xiangjun Lai (Forest Chemicals Review, 2022)
With the maturity of mobile Internet and the continuous penetration of large data into various industries, catering chains have already possessed certain large data operation capabilities. From the perspective of chain catering enterprises, this paper analyses the basic concepts of member network marketing based on big data, and the differences between them and traditional marketing, and combines with the current market environment and technological development of catering industry, to analyze why network marketing based on big data is imperative. At the same time, based on the RFM model, user retention growth model and customer life cycle theory, this paper puts forward the network marketing strategy of catering members based on large data for the characteristics of catering chain marketing.